PENGARUH JENIS GULA DAN PENAMBAHAN SARI NANAS-WORTEL TERHADAP SIFAT FISIKO-KIMIA, VIABILITAS BAKTERI YOGURT, SERTA ORGANOLEPTIK YOGURT NON FAT - Wijaya, Caroline; Kusumawati, Netty; Nugerahani, Ira (Jurnal Teknologi Pangan dan Gizi, 2012)
Yogurt is a dairy products through fermentation lactic acid bacteria (LAB) by Lactobacillus delbrueckii ssp. bulgaricus dan Streptococcus salivarius ssp. thermophilus. Isomalt has a lower caloric value can be used in yogurt. Addition of pineapple-carrot juice can also be done as a natural coloring gents, aroma and flavor enhancer in yogurt. The experimental design was a nested Randomized Block Design (RBD) with type of sugar (as the nest) consist of sucrose and isomalt, and pineapple-carrot juice addition (as the nested part) consist of 3 levels of 20%, 25%, and 30% with 4 replications for each treatment. The parameters observed were pH, acidity, syneresis, total LAB and sensory (preferences of taste, color, and aroma). Data statistically analyzed by ANOVA (Analysis of Varians) at Î± = 5%. If there was a significant difference, then it was continued by DMRT (Duncan's Multiple Range Test) test to determine which level of treatment that showed significant differences. Increased concentration of pineapple-carrot juice reduced pH, meanwhile acidity, syneresis, and viability of LAB were increased. The best yogurt in this research were yogurt with sucrose (30% pineapple carrot juice) with pH 4,442, acidity 34,48oSH, syneresis 1,87%, total of LAB 10,4491 log cfu/mL, consumer perception defined as neutral for color, rather liked for taste and aroma, and yogurt with isomalt (25% pineapple carrot juice) with pH 4,468, acidity 34,75oSH, syneresis 2,31%, total of LAB 10,2410 log cfu/mL, consumer perception defined as rather liked for color, neutral for aroma, and rather not liked for taste.